Productivity of Online Learning Media in Education Management - Dian Cita Sari; Fahri Zalmi; Akhyak Akhyak (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: The productivity of online learning media for implementing learning has increased intensely since the corona lockdown. This presents a challenge to improve knowledge by developing media so that students have more time to study independently during the lockdown period.: Background Problems: Researchers compared the productivity of various learning media such as text, video, and video-text combinations.: Novelty: Statistical analysis using Mann Whitney showed significant differences in knowledge retention between the text and video groups and between the video and text-video combination groups. Research Methods: This study was conducted using a quasi-experimental post-test method by comparing participants' retention before the intervention. Finding/Results: The study involved 60 participants who were randomly divided into three groups, text (guidebook), audiovisual (video), and text-video combination. Video and text prepared by Widyaiswara. The results showed that the average scores were 35.1 (text group), 58.1 (video group), and 85.2 (text-video combination group). Conclusion: use of multimedia can increase knowledge retention in the absorption of the material.